PENGHITUNGAN KAPASITAS RISIKO PERUSAHAAN ASURANSI DENGAN PENDEKATAN ALTMAN Z-SCORE STUDI KASUS PT JASA RAHARJA - Setyawan, Ujang; Sunaryo, Tarsicius; Tambunan, Martua E. (Universitas Muhammadiyah Pontianak, 2026)
State-owned social insurance company PT Jasa Raharja plays a strategic role in financial stability through risk management. This study assesses its financial risk capacity from 2020 to 2024 using the Modified Altman Z-Score for Emerging Markets. Results show consistent placement in the Safe Zone, with Z-Scores ranging from 3.88 (2020) to 3.20 (2024), indicating very low bankruptcy risk. However, risk capacity in Rupiah declined significantly from IDR 9.53 trillion to IDR 6.28 trillion due to rising liabilities, especially technical reserves. This signals a narrowing financial safety margin, requiring enhanced asset